Discourse on Myths & Suicide Fatalities in Sumelang Seagrass Film - Abudi, Anggun Wahyuningsi MK.; Narway, St. Tri Guntur; Siva, Nur (Journal of Language Development and Linguistics, 2025)
This study aims to explore the discourse of myth and suicide fatality depicted in the film Lamun Sumelang. Norman Fairclough's critical discourse analysis theory is used in this study and based on the results of the analysis, the film Lamun Sumelang basically interprets the myth as a belief that develops among the people in Gunung Kidul and becomes a cultural culture even though the myth cannot be proven scientifically. The myth of pulung gantung is considered a bad omen. Meanwhile, suicide fatality in the film Lamun Sumelang is depicted as a manifestation of despair, loneliness, and giving up on circumstances. However, on the other hand, it also illustrates the desire for other people's attention to the situation at hand.